1999
DOI: 10.1021/bi991353h
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of High-Affinity Peptide Antagonists of 14-3-3 Proteins by Phage Display

Abstract: The 14-3-3 proteins interact with diverse cellular molecules involved in various signal transduction pathways controlling cell proliferation, transformation, and apoptosis. To aid our investigation of the biological function of 14-3-3 proteins, we have set out to identify high-affinity antagonists. By screening phage display libraries, we have identified a set of peptides which bind 14-3-3 proteins. One of these peptides, termed R18, exhibited a high affinity for different isoforms of 14-3-3 with estimated K(D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
252
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(271 citation statements)
references
References 47 publications
14
252
0
1
Order By: Relevance
“…The ability of 14-3-3 to bind nonphosphorylated peptides and proteins has been demonstrated by several groups; however, the physiological relevance of this potential has not been determined (Petosa et al, 1998;Masters et al, 1999;Wang et al, 1999). Our finding showing that the in vivo 14-3-3-associated proteins in COS-7 cells bind 14-3-3 through the phosphopeptide binding groove, as demonstrated by the ability of a 14-3-3 binding phosphopeptide to displace all specifically associated proteins, combined with the finding that most of these associated proteins are reactive with the pan phospho-specific 14-3-3 binding site antibody, raises questions about the physiological significance of 14-3-3 binding to nonphosphorylated targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of 14-3-3 to bind nonphosphorylated peptides and proteins has been demonstrated by several groups; however, the physiological relevance of this potential has not been determined (Petosa et al, 1998;Masters et al, 1999;Wang et al, 1999). Our finding showing that the in vivo 14-3-3-associated proteins in COS-7 cells bind 14-3-3 through the phosphopeptide binding groove, as demonstrated by the ability of a 14-3-3 binding phosphopeptide to displace all specifically associated proteins, combined with the finding that most of these associated proteins are reactive with the pan phospho-specific 14-3-3 binding site antibody, raises questions about the physiological significance of 14-3-3 binding to nonphosphorylated targets.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several reports indicate that 14-3-3 proteins can also bind nonphosphorylated peptides and proteins through their phosphopeptide binding pocket (Masters et al, 1999;Wang et al, 1999;Mils et al, 2000). To examine what fraction of the 14-3-3-associated proteins in COS-7 cells contains phosphorylation sites recognized by the pan phosphospecific 14-3-3 binding site antibody, we compared the pattern of 14-3-3-associated proteins detected by metabolic 35 SMet labeling (Figure 2, top) with that detected by immunoblotting with the pan phospho-specific antibody (Figure 2, bottom).…”
Section: Most Of the 14-3-3-associated Proteins In Cos-7 Cells Arementioning
confidence: 99%
“…R18 (PHCVPRDLSWLDLEANMCLP) is a potent 14-3-3 peptide antagonist, which disrupts binding of Ser/Thr phosphorylated proteins to 14-3-3 (Wang et al, 1999). We generated a recombinant R18-green fluorescent protein expressing herpes simplex virus (HSV-R18-GFP) and a control HSV-WLRL-GFP virus that does not bind to 14-3-3 because of a substitution in the core-binding motif (WLDL to WLRL) (Wang et al, 1999). R18-GFP binds to 14-3-3 and antagonizes a previously characterized 14-3-3 -Slingshot1 interaction (supplemental Fig.…”
Section: -3-3 Proteins Are Expressed In Neuronal Growth Conesmentioning
confidence: 99%
“…Analysis of the AvrRxv sequence indicated that there are two domains in AvrRxv that resemble known 14-3-3 binding motifs, RSFDTP (called Raf domain) and MDIE (called R18 domain) [42,45]. To test if either the Raf or R18 domain is important for the AvrRxv and ARI1 interaction, mutant versions of AvrRxv were assayed for interaction with ARI1 in yeast.…”
Section: Mutational Analysis Of 14-3-3 Protein-binding Sequence Motifmentioning
confidence: 99%
“…This motif is called the Raf motif because it was first identified in the Raf-1 protein kinase. In addition, there is a 14-3-3 binding motif that does not require phosphorylation called the R18 motif, found in an inhibitory peptide (DI/L/VE) [42]. Although the vast majority of 14-3-3 interactions require phosphorylation, it is not required for binding of 14-3-3 proteins to several cellular proteins in mammals, most importantly, the ADP-ribosyltransferase effector ExoS of Pseudomonas aeruginosa [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%